Terrible Typhoid Mary: a true story of the deadliest cook in America (Houghton Mifflin Harcourt, 2015)
Tells the story of "Typhoid" Mary Mallon, a cook in the early twentieth century who was a carrier for typhoid fever and sickening dozens.
In which Mrs. Warren has a servant problem , In which the Warrens get more than their just dessert , In which the usual suspects are questioned , In which an epidemic fighter hunts for a clue , In which the cook rules the kitchen , In which Mary walks more like a man than a woman , In which extraordinary and arbitrary powers are at work , In which Mary fights like a caged lion , In which Mary's bad behavior leads to her doom , In which there's some name calling , In which Mary is banished like aleper , In which Mary has her day in court , In which Mary learns to keep her germs to herself , In which it takes a squad of sanitary police , In which a weaker spirit might have been broken , Afterword, in which we consider the research and writing of Mary's life.